Computer aided geometric design: application of quartic bezier curve in designing Spiral Batik / Nurul Syahida Zulkofli - Zulkofli, Nurul Syahida (2017)
The construction of Bezier curves is one of the most popular areas of research in computer aided geometric design (CAGD). In this research, a quartic Bezier method was developed in designing spiral Batik. This research proposed the field of designing Batik by implemented and tested the method using MATHEMATICA. This project deals with the design and development of new tool for designing batik. The impact of the study is to recommend on the use of innovative computer-aided geometric design in designing Batik. Finally, the experimental results have shown its effectiveness and the potential ability to be a useful tool for Batik design. The findings are then summarized with some recommendations suggested for the future research.